Membela Iman dengan Akal: Kontribusi Anselmus bagi Kritik Anti Intelektualisme Teologis (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the contribution of Anselmus dari Canterbury in addressing the tendency of anti-intellectualism in certain theological practices that separate faith from reason. The background of this research lies in the growing assumption that faith does not require philosophical reflection, which often leads to subjective and uncritical interpretations of sacred texts. The objective of this study is to analyze Anselm’s concept of fides quaerens intellectum as a framework for integrating faith and reason. This research employs a qualitative method with a philosophical and hermeneutical approach, focusing on textual analysis of Anselm’s works and relevant scholarly literature. The findings show that Anselm does not oppose faith and reason but emphasizes that faith naturally seeks understanding. This integration prevents arbitrary interpretations and strengthens the rational foundation of belief. The study implies that Anselm’s thought remains relevant for contemporary theological discourse, especially in promoting a balanced and critical understanding of faith in modern religious contexts.